The Native Symbols Engaging Turkish Players to Digital Games in a Playability Perspective. (August 2017) - Aslan, Alper; Coban, Murat; Karakus Yilmaz, Turkan; Goktas, Yuksel
Background. The satisfaction of a player's gaming experience has a great impact on theirgame preferences . The goal of this study was to investigate the opinions and experiences ofTurkish players ofcomputer games in order to examine the effects ofnative symbols on theirgame preferences . Method. The data collection tools were games developed in Turkey, websites for these games, user comments made on the video records of the games, online forums, and an open-ended questionnaire. Results. The results indicate that althoughnative symbols from the players' home society play a role in shaping the users'playability perception, it cannot be argued that they change thegame preference s. These results may be applied tocomputer games ' designs, development strategies, and advertising methods to attract all players.